2010
DOI: 10.1111/j.1443-1661.2010.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Endoscopy for Obscure Gastrointestinal Bleeding in the Tropics: Report From India

Abstract: CE is safe and is equally effective in detecting lesion(s) in occult and overt OGIB. Worm infestation and small bowel tuberculosis are unique and important causes of OGIB in the tropics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The finding that small bowel ulcer, instead of angiodysplasia was the most common cause of OGIB in this study needs attention. Angiodysplasia is well-known to be the most common cause of OGIB among Western patients but no convincing data to show that this holds true among Asians [18][19][20][21] . Some [18,20] reported angiodysplasia as a main cause of OGIB, while others [19,21] report ulcers to be the main etiology.…”
Section: Characteristics Of Patients According To the Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that small bowel ulcer, instead of angiodysplasia was the most common cause of OGIB in this study needs attention. Angiodysplasia is well-known to be the most common cause of OGIB among Western patients but no convincing data to show that this holds true among Asians [18][19][20][21] . Some [18,20] reported angiodysplasia as a main cause of OGIB, while others [19,21] report ulcers to be the main etiology.…”
Section: Characteristics Of Patients According To the Etiologymentioning
confidence: 99%
“…Angiodysplasia is well-known to be the most common cause of OGIB among Western patients but no convincing data to show that this holds true among Asians [18][19][20][21] . Some [18,20] reported angiodysplasia as a main cause of OGIB, while others [19,21] report ulcers to be the main etiology. However, when considered large studies that include more than 100 patients, one study from India [21] and two double-balloon enteroscopy studies from Japan [22,23] , all showed that small bowel ulcers were the most common cause of OGIB (41%-53%), more common than angiodysplasia (23%-24%).…”
Section: Characteristics Of Patients According To the Etiologymentioning
confidence: 99%
“…3 The detection rate for source of bleed for CE among patients with obscure GI in our study is similar to already published literature. [4][5][6][7] In our study angioectasia was the commonest etiology in patients presenting withOGIB.Hookworm infestation was diagnosed in two out the nine patients with OGIB which is an interest finding that is not being reported in similar studies in western population. Among the two patients with hookworm infestation, one presented with overt GI bleed in the form of melena with severe anemia which required multiple packed red blood cell transfusion and the other presented with occult GI bleed with iron deficiency anemia.…”
Section: Discussionmentioning
confidence: 42%
“…Ghoshal et al evaluated CE in obscure GI bleed in 86 patients and found hookworm infestation in 7.8%. 5 The diagnostic yield of CE endoscopy depends on the optimum timing which is ideally within the 48 hours of the bleed but can be extended up to a maximum of 2 weeks and the presence of overt or occult GI bleed where the diagnostic yield were much higher (87% vs 46%) in patients presenting with overt GI bleed . 4 The remaining cases in our study with regard to obscure GI bleed had more than one lesion noted such as a combination of angioectasia with small bowel ulcers or polyp.…”
Section: Discussionmentioning
confidence: 99%
“…Most series showed that lesions are detected more often in patients with obscure overt than occult gastrointestinal bleeding [25], [26] though a few series did contradict this observation. [27] It has also been shown that if capsule endoscopy is performed early after a bleeding episode, it detects lesion more frequently than if it is done late. In some studies, authors showed that second capsule endoscopy may pick-up some of the lesions missed by first study.…”
Section: Small Bowel Capsule Endoscopy: the Methodsmentioning
confidence: 99%